COMPETENCY-BASED TEACHER EVALUATION: EVALUATING TEACHERS' PEDAGOGIC AND SOCIAL SKILLS - Risha Febriyanti; Suharry; Andri Yuliandi; Ambiyar; Mahesi Agni Zaus (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Teacher performance assessment has not been optimal so far because it is not competency-based. Evaluation of teacher competencies is needed to improve the quality of learning. The purpose of this study is to evaluate the pedagogical and social competence of teachers based on teacher performance assessment instruments set by the Ministry of Education and Culture. This study uses a qualitative approach with a case study method. The subjects of the study are 10 teachers at SMKN 2 Sungai TFull Data collection instruments include classroom observation and interviews. The evaluation results showed that the teacher's pedagogic competence was good enough for the aspects of learning planning, material collection, and learning model. However, some teachers need to improve their social competence, especially communicating and cooperating. Teacher competency evaluation based on performance assessment instruments has proven to be effective in evaluating and improving teacher competencies in a standardized and comprehensive manner. To improve performance even more, teachers need to continue to follow self-development programs.